Blood Cell Profile of the Developing Tadpoles and Adults of the Ornate Frog, Microhyla ornata (Anura: Microhylidae) - Hota, Jutshina; Das, Madhusmita; Mahapatra, Pravati Kumari (International Journal of Zoology, 2013)
Metamorphosis happens to be an important event in the lifetime of amphibians. Our study offers a record of blood cell profile of laboratory reared tadpoles during development and metamorphosis (Gosner stage 26 to 46) and adults of Microhyla ornata. The larval erythrocytes were observed to be circular, oval, and elliptical in shape. However, other variations were distinct during the prometamorphic and metamorphic stages. Crenulated erythrocytes showed a pattern of appearance, and the crenulations varied from minute serrations to highly spiked projections. Correlations between the morphometric values of erythrocytes during the larval development were also determined. The leukocyte profile of the tadpoles showed a high percentage of lymphocytes during larval development while the percentage of monocytes, eosinophils, and neutrophils remained high during metamorphosis and were positively correlated with the developing stages. Blood thrombocytes of the tadpoles were small and were found in clusters. Elliptical erythrocytes were the most common in the adult frogs. However, few erythrocytes were also circular in shape. In adults, the percentage of lymphocytes was found to be more in comparison with the other leucocytes, and neutrophils showed various polymorphic forms. Thrombocytes were nucleated and spindle shaped.